Respostas
respondido por:
1
a)
adição- vamos cancelar o x e somar
fica
8y=0
y=0
substituir y em
5x-6y=20
5x-6(0)=20
5x=20
x=20÷5
x=4
S={(4,0)}
b)
cancela o y e somar
fica
-2y=-2
2y=2
y=2÷2
y=1
substituir y em
2x-3y=-7
2x-3(1)=-7
2x-3=-7
2x=-7+3
2x=-4
x=-4÷2
x=-2
S={(-2,1)}
c)
cancela o y e soma
fica
4x=36
x=36÷4
x=9
substituir x em
x+4y=4
9+4y=4
4y=4-9
4y=-5
y=-5/4
S={(9,-5/4)}
adição- vamos cancelar o x e somar
fica
8y=0
y=0
substituir y em
5x-6y=20
5x-6(0)=20
5x=20
x=20÷5
x=4
S={(4,0)}
b)
cancela o y e somar
fica
-2y=-2
2y=2
y=2÷2
y=1
substituir y em
2x-3y=-7
2x-3(1)=-7
2x-3=-7
2x=-7+3
2x=-4
x=-4÷2
x=-2
S={(-2,1)}
c)
cancela o y e soma
fica
4x=36
x=36÷4
x=9
substituir x em
x+4y=4
9+4y=4
4y=4-9
4y=-5
y=-5/4
S={(9,-5/4)}
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás